UPAYA PENINGKATAN PELAYANAN PERIZINAN MELALUI SISTEM PELAYANAN TERPADU SATU PINTU PADA DINAS PENANAMAN MODAL KOTA JAMBI - Ayu Tantri, Novia; Budhiartie, Arrie (Mendapo: Journal of Administrative Law, 2021)
This paper was written to find out how the one-stop integrated service system at the Jambi City Investment Agency can improve the process of better licensing services. Reform of public service policies, especially in matters of licensing, is an activity that encourages the development of the formal economic sector. Therefore, it is necessary to know how to regulate the one-stop integrated licensing service procedure at the Jambi City One Stop Integrated Investment Service, to know what are the constraints in the implementation of one-stop integrated services at DPMPTSP Jambi City, and how the efforts to increase licensing are carried out at the One Integrated Investment Office Jambi City Door.